Bibliometric Analysis of the Ability to Solve Algebra Problems in Elementary School AKM Numeracy Context - Wijaya, Budi; Mariana, Neni; Rahaju, Endah Budi (Indonesia Emerging Literacy Education, 2024)
Objective: The purpose of this bibliometric analysis is to look at opportunities and trends in research related to the completion of algebra context numeration Assessment of Minimum Competence at the level of Elementary School using the VOS Viewer application. Method: The method used in this research is bibliometric, collecting data from articles or journals from 2021 to 2023 through the Google Scholar site using the Publish or Perish software of 500 articles or magazines. Results: Similar research results show that in 2021, there were 101 publications; in 2022, there were 166; and in 2023, there were 198. The number of quotes was 2097; the average quotation per year was 699; the quotations per paper was 4.51; the averages per writer were 1,222.65; the median number of papers/writers was 293.32; and the average number of writers/publishers was 2.09. Novelty: Variables related to the completion of algebra issues through the Minimum Competence Assessment at the elementary school level that have the opportunity and novelty to be studied in the future are in the context category of numeration consisting of personal, social, cultural, and scientific.